Synthesis and evaluation of carbamate derivatives as fatty acid amide hydrolase and monoacylglycerol lipase inhibitors - Jaiswal S.; Gupta G.; Ayyannan S.R. (My University, 2025)
Fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) are the primary catabolic enzymes for endocannabinoids, anandamide (AEA), and 2-arachidonoyl glycerol. Numerous studies have shown that FAAH and MAGL play an important role in modulating various central nervous system activities; hence, the development of small molecule FAAH/MAGL inhibitors is an active area of research. Several small molecules possessing the carbamate scaffold are documented as potential FAAH/MAGL inhibitors. Here, we designed and synthesized a series of open chain and cyclic carbamates and evaluated their dual FAAH–MAGL inhibition properties. Phenyl [4-(piperidin-1-ylmethyl)phenyl]carbamate (2e) emerged as the most potent MAGL inhibitor (IC50 = 19 nM), benzyl (1H-benzo[d]imidazol-2-yl)carbamate (3h) was the most potent FAAH inhibitor (IC50 = 55 nM), and phenyl (6-fluorobenzo[d]thiazol-2-yl)carbamate (2i) egressed as a nonselective dual FAAH–MAGL inhibitor (FAAH: 82 nM, MAGL: 72 nM). The enzyme kinetics experiments revealed that the compounds inhibit FAAH/MAGL in a covalent-reversible manner, with a mixed binding mode of action. Moreover, the lead compounds were found suitable for blood–brain permeation in the parallel artificial membrane permeation assay. Furthermore, docking simulation experiments suggested that the potency of the lead compounds was governed by hydrogen bonds and hydrophobic interactions with the enzyme active sites. In silico drug-likeness and ADMETox prediction studies provided useful information on the compounds' oral absorption, metabolism, and toxicity profiles. In summary, this study afforded potent multifunctional carbamates with appreciable pharmacokinetic profiles meriting further investigation. © 2022 Deutsche Pharmazeutische Gesellschaft.